2019
DOI: 10.1186/s12864-018-5412-4
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin fusion proteins in algae: implications for cell biology and the spread of photosynthesis

Abstract: BackgroundThe process of gene fusion involves the formation of a single chimeric gene from multiple complete or partial gene sequences. Gene fusion is recognized as an important mechanism by which genes and their protein products can evolve new functions. The presence-absence of gene fusions can also be useful characters for inferring evolutionary relationships between organisms.ResultsHere we show that the nuclear genomes of two unrelated single-celled algae, the cryptophyte Guillardia theta and the chlorarac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Only rarely, Ub is fused to other proteins in different architectures ( Table S2 ), although these arrangements are widely represented in the eukaryotic groups of animals, fungi, and plants ( Figure 3 ). In this sense, in a small group of mixotrophic algae, it has been reported that one or several N-terminal Ub moieties are fused in-frame inter alia to ribosomal protein P1, actin, a zinc-finger protein, a nickel superoxide dismutase, or a protein with similarity to bacterial integral membrane proteins [ 35 , 36 ]. A more careful study indicates that the Ub fusion to the latter three proteins is found in other eukaryotes, such as different types of algae and diverse fungi [ 36 ].…”
Section: The Ubiquitin Genes In Eukaryotesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only rarely, Ub is fused to other proteins in different architectures ( Table S2 ), although these arrangements are widely represented in the eukaryotic groups of animals, fungi, and plants ( Figure 3 ). In this sense, in a small group of mixotrophic algae, it has been reported that one or several N-terminal Ub moieties are fused in-frame inter alia to ribosomal protein P1, actin, a zinc-finger protein, a nickel superoxide dismutase, or a protein with similarity to bacterial integral membrane proteins [ 35 , 36 ]. A more careful study indicates that the Ub fusion to the latter three proteins is found in other eukaryotes, such as different types of algae and diverse fungi [ 36 ].…”
Section: The Ubiquitin Genes In Eukaryotesmentioning
confidence: 99%
“…In this sense, in a small group of mixotrophic algae, it has been reported that one or several N-terminal Ub moieties are fused in-frame inter alia to ribosomal protein P1, actin, a zinc-finger protein, a nickel superoxide dismutase, or a protein with similarity to bacterial integral membrane proteins [ 35 , 36 ]. A more careful study indicates that the Ub fusion to the latter three proteins is found in other eukaryotes, such as different types of algae and diverse fungi [ 36 ]. Indeed, our analysis shows that the zf-AN1 (PF01428) and zf-RRN7 (PF11781) domains, which correspond to zinc-finger domains, are the most abundant ones in these unusual architectures (ca.…”
Section: The Ubiquitin Genes In Eukaryotesmentioning
confidence: 99%
“…In both humans and mice, there are four genes encoding ubiquitin: UBB and UBC encoding polyubiquitin precursor with ubiquitin repeats and RPS27A/eS31 and UBA52 encoding ubiquitin as in-frame fusions to RPS27A/eS31 and RPL40/eL40, respectively ( Park and Ryu, 2014 ). These RP-ubiquitin fusions (ubiquitin-S27A/L40) are identified across the full breadth of eukaryotic diversity ( Sibbald et al, 2019 ). Ubiquitin can be posttranslationally cleaved from RP–ubiquitin fusions.…”
Section: Introductionmentioning
confidence: 99%
“…For both classes, free de novo ubiquitin is synthesized by proteolytic maturation from the corresponding precursor proteins. Only rarely, ubiquitin is encoded by monoubiquitin genes, as occurs in the protozoa Giardia lamblia and Entamoeba histolytica , or in algae as Guillardia theta and Bigelowiella natans [11,12,13].…”
Section: Introductionmentioning
confidence: 99%